Oxford international primary English student book 5 - Barber, Alison (Oxford Oxford university press, 2021)
Oxford International English Book 5 is part of a comprehensive series designed to support learners in developing their reading, writing, listening, and speaking skills in English. Aligned with international curriculum standards, it offers engaging texts, stimulating activities, and a range of genres to enhance language proficiency and critical thinking. The book promotes a balanced approach to learning through creative tasks, comprehension exercises, and vocabulary building, making it ideal for students in global educational settings.